2021
DOI: 10.1371/journal.ppat.1008603
|View full text |Cite
|
Sign up to set email alerts
|

DENV NS1 and MMP-9 cooperate to induce vascular leakage by altering endothelial cell adhesion and tight junction

Abstract: Dengue virus (DENV) is a mosquito-borne pathogen that causes a spectrum of diseases including life-threatening dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Vascular leakage is a common clinical crisis in DHF/DSS patients and highly associated with increased endothelial permeability. The presence of vascular leakage causes hypotension, circulatory failure, and disseminated intravascular coagulation as the disease progresses of DHF/DSS patients, which can lead to the death of patients. However… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 33 publications
(55 reference statements)
1
30
0
Order By: Relevance
“…In our study, we observed that DTMUV-infected DEF included a number of upregulated DEG that regulate the action cytoskeleton signaling pathway, such as FGF (fibroblast growth factor) family members (FGF1/3/4/5/19) and scaffold protein IQGAP2, which play a role in stabilizing microtubules [ 34 36 ] (Figure 6 ). Then, we found that tight junction (CGN, MAP3K5, GATA4 and RUNX1) and focal adhesion (KDR, LAMA3, LAMC2, PTK2, COL6A6 and COL4A3) play important roles in DTMUV replication, which is similar to the reports of flavivirus [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 78%
“…In our study, we observed that DTMUV-infected DEF included a number of upregulated DEG that regulate the action cytoskeleton signaling pathway, such as FGF (fibroblast growth factor) family members (FGF1/3/4/5/19) and scaffold protein IQGAP2, which play a role in stabilizing microtubules [ 34 36 ] (Figure 6 ). Then, we found that tight junction (CGN, MAP3K5, GATA4 and RUNX1) and focal adhesion (KDR, LAMA3, LAMC2, PTK2, COL6A6 and COL4A3) play important roles in DTMUV replication, which is similar to the reports of flavivirus [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 78%
“…DENV nonstructural protein-1 (NS1) is a highly conserved 48-kDa membrane-associated glycoprotein. Interestingly, NS1 is the only nonstructural viral protein secreted by infected host cells [ 12 ], and circulating levels of NS1 correlated positively with vascular permeability in vitro and in vivo [ 5 , 8 , 13 , 14 ]. However, other clinical studies have not shown a correlation between NS-1-induced vascular permeability.…”
Section: Dengue Nonstructural Protein 1: a Mediator Of Vascular Hyperpermeabilitymentioning
confidence: 99%
“…NS1 also interacts with Toll-like receptor (TLR) 4 and induces the production of proinflammatory and vasoactive mediators including cytokines and vascular growth factors, many of which are likely to cause damage to EGL and inducing vascular pathology [ 18 20 ]. Two noteworthy molecules induced by NS1 are matrix metalloproteinases (MMPs) produced by leukocytes and macrophage inhibitory factor (MIF) secreted by endothelial cells [ 13 , 21 ]. EGL components such as syndecan-1, syndecan-2, and syndecan-4 can be cleaved by MMP-9, and this process may be further enhanced through MIF.…”
Section: Dengue Nonstructural Protein 1: a Mediator Of Vascular Hyperpermeabilitymentioning
confidence: 99%
See 2 more Smart Citations